Pengembangan Bahan Ajar Smartboardbook Berbasis Augmented Reality pada Pembelajaran IPAS Materi Kekayaan Budaya Indonesia Kelas IV SDIT Al-Farabi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2026)
This study aims to develop Smartboard Book teaching materials based on Augmented Reality that are valid, practical, and effective for improving students' learning outcomes in the IPAS (Science) subject for grade IV at SDIT Al-Farabi. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of this study were grade IV students at SDIT Al-Farabi. Data collection techniques were conducted through expert validation questionnaires, response questionnaires, and learning outcome tests. The results indicate that the Smartboard Book teaching material was declared very valid, with material and test instrument validation percentages of 88% and media validation of 95%. The teaching material was also declared practical based on teacher and student responses. Furthermore, this media proved to be effective in improving students' learning outcomes with an N-gain score of 0.86, which falls into the high category. Based on these findings, it is recommended that teachers utilize Smartboard Book teaching materials based on Augmented Reality as an alternative medium in learning activities to create a more interactive and engaging learning environment.